Effects of Oral Polyethylene Microplastic Dose on Wistar Rats’ Cognition Assessed by Morris Water Maze - Michael Yohanes Kuncoro; Nita Kurniawati; Yudhiakuari Sincihu; Pauline Meryana; L. Suwandito (Environmental Pollution Journal, 2026)
Orally ingested polyethylene (LDPE) microplastics are suspected to impair cognitive function through disturbances in the central nervous system, particularly in cognitive regions such as the cortex and hippocampus. This study aims to evaluate the effect of varying oral doses of LDPE microplastics on the cognitive function of Wistar Rattus norvegicus using the Morris Water Maze (MWM) test. This experimental study employed a post-test only control group design involving 21 male Wistar rats divided into four groups: a control group and three treatment groups receiving LDPE microplastics at low dose and high dose administered orally for 28 days (particle size ≤20 µm). Cognitive function was assessed using the latency time to locate the hidden platform in the MWM and analyzed statistically. The mean latency tended to increase with increasing dose. Using the control group as the baseline, there was a slight increase in the outcome in the low dose group, and a markedly higher increase observed in the high dose group. Statistical analysis showed a significant difference between the control group and the high dose group (p = 0.009). Oral administration of LDPE microplastics at  high dose for 28 days was associated with a significant impairment in cognitive function.